Comparison of Ibuprofen and Dexamethasone Premedication on Inferior Dental Nerve Block in Irreversible Pulpitis - Dilawar Sultan, Anila Hidayat, Dania Sohail, Waqar Ali, Khaqan Azam, Muhammad Khizar Mannan, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare premedication with dexamethasone as compared to ibuprofen in the effectiveness of IDNB in lower molars with asymptomatic irreversible pulpal infection. Study design: A Randomized Control Clinical Trial. Place & duration: Department of Operative Dentistry, Akhtar Saeed Medical and Dental College, Lahore, from October 2022 to November 2022 Methodology: A total of 30 cases in each group were taken, using an expected success rate of Dexamethasone group and Ibuprofen group 38.2% and 78% respectively, taking 5% level of significance 80% power of study. Therefore, sixty endodontic subjects were taken and divided into two equal groups of thirty patients each, group 1 was given 0.5 mg dexamethasone and group 2, was given 400 mg ibuprofen as pre-medication prior to endodontic therapy. Results: The results showed mean pain scores 24.38±15.41 in group 1 and 35.63±18.74 in group 2 (P<0.05). According to pain score, 11 patients (36.7%) have pain score between 0.0-20 (successful) and 21 patients (63.3%) has pain score 21.0-100.0 (unsuccessful) in group 1 with mean±standard deviation of 24.38±15.41. While in group 2, 5 patients (16.7%) have pain score 0.0-20 and 25 patients (83.3%) have pain score 21.0-100.0 with mean±standard deviation of 35.63±18.74. Conclusion: The premedication with dexamethasone as compared to ibuprofen, increased the effectiveness of inferior dental nerve block in lower molars with asymptomatic irreversible pulpitis. Keywords: IDNB, Irreversible pulpitis, Nerve block, Endodontics.